INOVASI PEMBELAJARAN DAN PENELITIAN SAINS UNTUK MEMBANGUN PROFESIONALISME PENGAJAR - Zeni Haryanto (Universitas Lambung Mangkurat, 2010)
Abstract. Teaching and learning innovation is the idea or practice that cause the change to be more potential and efficient to reach the aims of teaching and learning. Innovation can be carried out from the educational process or the input and output aspects. One of their indicators is implementing of appropriate instruction model in teaching and learning process and educational research. Implementation of innovative instructional model and educational research will also increase the teacher proffesionality.Key words: innonation, professionality, teaching and learning, and research